2011
DOI: 10.1002/ajmg.a.34223
|View full text |Cite
|
Sign up to set email alerts
|

Somatic mosaicism contributes to phenotypic variation in Timothy syndrome

Abstract: Timothy syndrome type 1 (TS-1) is a rare disorder that affects multiple organ systems and has a high incidence of sudden death due to profound QT prolongation and resultant ventricular arrhythmias. All previously described cases of TS-1 are the result of a missense mutation in exon 8A (p.G406R), an alternatively spliced variant of the L-type calcium channel gene (Ca(v)1.2, CACNA1C). Most patients reported in the literature represent highly affected individuals who present early in life with severe cardiac and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
58
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(62 citation statements)
references
References 15 publications
3
58
0
1
Order By: Relevance
“…1,7 Given these findings, it is clear that mosaicism contributes to the inheritance of TS1. Although we acknowledge this is not the first case in which a parent harboring limited presence of the canonical TS1 mutation has been affected by syndactyly alone, without any cardiac phenotype, this is the first case in which the diagnosis of this potentially lethal disorder was confounded by mosaicism.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1,7 Given these findings, it is clear that mosaicism contributes to the inheritance of TS1. Although we acknowledge this is not the first case in which a parent harboring limited presence of the canonical TS1 mutation has been affected by syndactyly alone, without any cardiac phenotype, this is the first case in which the diagnosis of this potentially lethal disorder was confounded by mosaicism.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies of mosaicism in Klinefelter' s syndrome have shown that mosaicism may affect the germline preferentially, with a mutation frequency of ,10% in blood lymphocytes and .36% in the gametes. 7 This observation, coupled with the fact that commercial genetic testing was unable to detect low-level CACNA1C-G406R mosiacism, suggests that a negative test result in the parent(s) of children with rare genetic disorders associated with germline mosiacism should be viewed with healthy skepticism, as these tests are optimized to detect heterozygous mutations (ie, 50% allelic frequency), rather than the low frequency (ie, ,10%) of the mutant allele present in the lymphocyte-derived gDNA of mosaic individuals. As such, clinicians may consider additional testing, particularly in cases in which an overlapping phenotype is observed, when using genetic test results to help parents make informed family planning decisions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, only 32 TS cases have been reported worldwide. [12][13][14] In this study, we identified the first case of TS in Chinese by genetic analysis and explored potential drug therapies for this malignant syndrome. The major novel findings of our study include: (1) a uncommon mosaicism in both germline and partial somatic inheritance for the CACNA1C-G406R mutation in TS; (2) worsening of functional 2:1 AVB and TWA in TS by use of either propranolol (a β-adrenergic receptor blocker) or diltiazem (a calcium channel blocker); and (3) abolishment of 2:1 AVB and TWA in TS by mexiletine via inhibition of I Na,L .…”
Section: Discussionmentioning
confidence: 99%
“…All previously described cases of TS-1 are associated with a missense mutation in exon 8A (p.G406R) of the Ltype calcium channel gene (Ca(v)1.2, CACNA1C). Most people reported in the literature represent highly affected individuals who present early in life with severe cardiac and neurological manifestations, but these authors found somatic mosaicism in TS-1 patients with less severe manifestations than the typical TS-1 patient [153]. There are therefore likely large ascertainment biases, given that people with much less expressive phenotypes are likely not coming to anyone's attention.…”
Section: "Those Who Have Given Any Attention To Congenital Mental Lesmentioning
confidence: 99%